Hubungan Infeksi Helicobacter Pylori terhadap Kejadian Gastritis Aktif dan Ulkus Duodenum: Study Literature - Agisni Fatihaturrohmah; Ayudia Shelina Audjah; Daaniys Aqila Halwa; Diva Tri Adzani; Firda Aulifia Sarah; Fitrio Danu Sudira; Muhammad Rizwan; Ovi Listiyani; Popi Sopiah (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
Helicobacter pylori infection is one of the main factors associated with the occurrence of active gastritis and duodenal ulcers. This bacterium can survive in the acidic environment of the stomach by producing the urease enzyme, allowing it to colonize the gastric mucosa and trigger an inflammatory response. This study aims to analyze the relationship between Helicobacter pylori infection and the incidence of active gastritis and duodenal ulcers. The method used was a literature review with a narrative approach of scientific articles published between 2021–2025 from the Google Scholar, OpenAlex, and Crossref databases. The results of the review indicate that Helicobacter pylori infection is significantly associated with increased gastric mucosal inflammation and a higher risk of duodenal ulcers. Early detection and eradication therapy using a combination of antibiotics and proton pump inhibitors (PPI) are effective in preventing disease progression and complications. Additional findings highlight the importance of hygiene, sanitation, and public awareness in reducing transmission rates and improving gastrointestinal health outcomes globally..